C-Abl inhibition; a novel therapeutic target for Parkinson’s disease - Abushouk, Abdelrahman Ibrahim; Negida, Ahmed; Abdelsalam Elshenawy, Rasha A; Zein, Hossam; Hammad, Ali M; Menshawy, Ahmed; Mohamed, Wael Mohamed Yousef (Bentham Science Publishers B.V., 2018)
Parkinson’s disease (PD) is the most prevalent movement disorder in the world. The major pathological hallmarks of PD are death of dopaminergic neurons and the formation of Lewy bodies. At the moment, there is no cure for PD; current treatments are symptomatic. Investigators are searching for neuroprotective agents and disease modifying strategies to slow the progress of PD. However, recently, due to the ignorance of the main pathological sequence of PD, many drug targets failed to provide neuroprotective effects in human trials. Currently, a huge amount of evidence suggests the involvement of C-Abelson (c-Abl) tyrosine kinase enzyme in the pathology of PD. C-abl plays a role in PD pathology on the levels of parkin activation, alpha synuclein aggregation, and impaired autophagy of toxic elements. Experimental studies showed that (1) c-abl activation is involved in neuronal death and (2) c-abl inhibition shows neuroprotective effects and prevents dopaminergic neurons’ death. Current evidence from experimental studies and the first in-human trial shows that c-abl inhibition holds the promise for neuroprotection against PD and therefore, justifies the movement towards larger clinical trials. In this review article, we discussed the role of c-abl in PD pathology and the findings of preclinical experiments and the first in-human trial. In addition, based on the lessons of the last decade and current preclinical evidence, we provide recommendations for future research in this area.